2021
DOI: 10.3389/fpls.2021.617815
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational Plasticity in Flower Color Induced by Caterpillars

Abstract: Variation in flower color due to transgenerational plasticity could stem directly from abiotic or biotic environmental conditions. Finding a link between biotic ecological interactions across generations and plasticity in flower color would indicate that transgenerational effects of ecological interactions, such as herbivory, might be involved in flower color evolution. We conducted controlled experiments across four generations of wild radish (Raphanus sativus, Brassicaceae) plants to explore whether flower c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 61 publications
0
18
1
Order By: Relevance
“…Differential effects of transgenerational plasticity on morphological and photosynthetic properties of invasive and native plants were found, which could be explained by adaptative strategies to maternal light treatment(Galloway 2005;Marin et al 2018). So, we tentatively concluded that effects of transgenerational plasticity on morphological and photosynthetic properties of offspring ramets were species-speci c.Transgenerational plasticity is regarded as particularly maternal environments may be affected the phenotypes of offsprings(González et al 2016;Li et al 2018;Mar et al 2021). Our results showed that maternal environment had a signi cant effect on biomass accumulation of W. trilobata, but had no signi cant effect of W. chinensis.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…Differential effects of transgenerational plasticity on morphological and photosynthetic properties of invasive and native plants were found, which could be explained by adaptative strategies to maternal light treatment(Galloway 2005;Marin et al 2018). So, we tentatively concluded that effects of transgenerational plasticity on morphological and photosynthetic properties of offspring ramets were species-speci c.Transgenerational plasticity is regarded as particularly maternal environments may be affected the phenotypes of offsprings(González et al 2016;Li et al 2018;Mar et al 2021). Our results showed that maternal environment had a signi cant effect on biomass accumulation of W. trilobata, but had no signi cant effect of W. chinensis.…”
mentioning
confidence: 56%
“…Phenotypes of plant offsprings may be affected by particularly maternal environmental conditions, which named as transgenerational plasticity (Galloway and Etterson 2007;González et al 2016; Mar et al 2021). Germination rate was signi cantly increased when seeds of Campanula americana were planted into their maternal light environment (Galloway 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We analyzed 188 samples from 94 plants in the F2 generation using two primer combinations. The To test whether herbivory was linked to the probability of occurrence of methylation per locus, we proceeded as follows (23). Because methylation and demethylation cannot occur at the same time, we considered nonmethylation events only when demethylation did not occur on the marker.…”
Section: Methodsmentioning
confidence: 99%
“…MSAP marker scores involving a change from 1 to 0 denoted a methylation event of the marker involved. Only fragments >300 base pairs in size were included to reduce the potential impact of size homoplasy (23). A new sample (n = 94 plant individuals) by marker (n = 402) score matrix was obtained, where each element showed whether the sample involved had experienced a methylation event (score = 1) or not (score = 0) in the corresponding marker (or missing when a demethylation event occurred and therefore a methylation event was not possible).…”
Section: Methodsmentioning
confidence: 99%
“…Kellenberger et al (2018) looked for transgenerational effects of herbivory in flower and reproductive traits of Brassica rapa and found that changes in flower volatiles were not transmitted to the next generation, but some morphological changes were maintained in subsequent generations. Other studies have found transgenerational effects of herbivory on flower traits like proportion of flowering plants and number flowers (Steets and Ashman, 2010;Nihranz et al, 2020) and flower color (Sobral et al, 2021). Interestingly, these types of effects may depend on the reproductive mechanism (cleistogamy vs. chasmogamy, Steets and Ashman, 2010) or inbreeding (Nihranz et al, 2020).…”
Section: Transgenerational Effectsmentioning
confidence: 98%